Integrated approach for assessing the fire risk of ethanol storage tank: A case study in ethanol manufacturing plant in Ubon Ratchathani Province, Thailand - Ratchanee Joomjee; Arroon Ketsakorn (Results in Engineering)
Assessing fire hazards is critical for enhancing safety in ethanol storage facilities, where highly flammable vapors pose serious risks to workers, infrastructure, and surrounding communities. This study presents an integrated risk assessment framework that combines Fault Tree Analysis (FTA), the Analytic Hierarchy Process (AHP), and the ALOHA (Areal Locations of Hazardous Atmospheres) model to evaluate both the probability and severity of potential fire incidents. FTA was employed to identify hazards and critical failure pathways, with process mapping supported by a piping and instrumentation diagram (P&ID), while AHP used expert judgment validated through pairwise comparisons to calculate the probabilities of human and technical errors. ALOHA simulated fire scenarios, estimating thermal radiation impact zones and categorizing hazards into red, orange, and yellow zones representing decreasing severity. Results indicated an overall fire probability of 88.10 %, with primary contributors including human error (86.09 %), equipment failure (77.15 %), tank leakage (70.15 %), and pipe leakage (69.80 %). The framework effectively identified high-risk components, predicted affected radii, and informed targeted risk management measures such as enhanced maintenance protocols, workforce training, and safety buffer zone design. Adaptable to other high-risk industrial contexts such as chemical manufacturing, fuel distribution, and hazardous material storage the approach offers a practical decision-support tool for industrial engineers and safety managers, with the potential to reduce accident-related costs, minimize operational downtime, and improve community safety.